Implementation of the Project-Based Learning (PjBL) Method in Islamic Religious Education Subjects to Enhance Student Engagement - Marleni M; Nia Asmara; Meli Indah Novitasari; Muhamad Iqbal; Siti Afifatun (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine the implementation of the Project Based Learning (PjBL) method in Islamic Religious Education (PAI) subjects to improve student activeness through a literature study approach. The literature review was conducted by examining various scientific sources, including national and international journal articles, reference books, seminar proceedings, and relevant educational policy documents published between 2010 and 2024. The results of the literature review indicate that PjBL is a project-based learning method that positions students as active subjects in the process of knowledge construction through authentic project work related to real-world problems. The application of PjBL in PAI learning has been shown to significantly promote student activeness, as reflected in increased involvement in discussions, critical thinking skills, creativity, and a sense of responsibility. Islamic values such as ta'awun (cooperation), amanah (trustworthiness), and mujahadah (striving) can be organically integrated into each phase of the project, making PAI learning not only academically meaningful but also transformative in terms of spirituality and character. Key success factors for implementation include teacher competence in designing contextual projects, learning facility support, and a conducive school climate. The study concludes that PjBL is worthy of being one of the innovative, student-centered alternative methods in PAI learning.